Spontaneous lymphocyte-mediated (NK cell) cytotoxicity in systemic sclerosis: a comparison with antibody-dependent lymphocyte (K cell) cytotoxicity. - Wright, J K (1982)
Spontaneous (NK cell) and antibody-dependent (K cell) cytotoxicity were investigated in 39 patients with systemic sclerosis (SS) and compared with that found in 52 normal controls. Cr-labelled Chang liver cells were used as targets in assays utilising both whole blood (WB) and peripheral blood mononuclear cells (PBM) as effectors. Patients with SS, who were severely affected by extensive visceral disease, were found to have significant impairment of both NK (p less than 0.005; p less than 0.05) and K (p less than 0.001; p less than 0.05) cell cytotoxicity by both effector systems, when compared with normal controls. These findings, which seem to be part of a wider defect in cell-mediated immunity, may provide a possible explanation for the described association of malignancy with systemic sclerosis.